Nitric oxide production induced by heavy metals in Brassica juncea L. Czern. and Pisum sativum L. - Bartha Bernadett (Acta biologica Szegediensis, 2005)
In plants, nitric oxide (NO) has multiple roles in defence reactions under abiotic stresses, including heavy metal load. Literature data suggest that there is a causal relationship between NO and iron metabolism but the effects of essential micronutrients/toxic heavy metals on NO production have not been investigated. In this study our aim is to demonstrate the possible role of NO in the plant response to heavy metals in the metal accumulator Brassica juncea and the crop plant Pisum sativum grown in the presence of either 100 μM cadmium, copper or zinc. NO production was measured in the root tips with fluorescent method, using 4,5-diaminofluorescein diacetate (DAF-2 DA), a specific dye to nitric oxide. We obtained different NO levels with the different heavy metal load: the most effective metal were copper and cadmium, in this case the NO production became double after one week treatment. In case of copper load, two-phase kinetics was found: a fast NO burst in the first six hours was followed by a slower, gradual increase. The fast appearance of NO in the presence of cupric ions suggest that it can be a novel reaction hitherto not studied in plants under heavy metal stress. After long-term treatment, NO levels were inversely related to the nitrite concentrations originated from nitrate reductase activity suggesting the conversion of nitrite to nitric oxide by the known enzymatic ways.